2012
DOI: 10.1074/jbc.m112.364851
|View full text |Cite
|
Sign up to set email alerts
|

The Dormancy Regulator DosR Controls Ribosome Stability in Hypoxic Mycobacteria

Abstract: Background: The mechanism by which mycobacteria maintain ribosome stability during latent infection is unknown.Results: Mycobacterium smegmatis uses a DosR-regulated S30AE domain protein, RafH, to maintain the associated (stable) ribosome during the hypoxia model of persistence.Conclusion: Ribosomal stability, mediated by RafH, is essential for survival and emergence from hypoxia.Significance: Learning how mycobacteria stabilize ribosomes to survive hypoxia is crucial for understanding latent tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 61 publications
(78 reference statements)
8
92
1
Order By: Relevance
“…Consistent with previous observations (30), the dosR mutant dramatically lost viability on induction of hypoxia. Complementation experiments have previously demonstrated that this phenotype is primarily, but not completely, due to loss of the ribosome-stabilizing factor RafH (32). Our experiments show that survival also depends on the combined activity of the three hydrogenases from M. smegmatis, all of which are up-regulated under oxygen limitation (14).…”
Section: Hydrogen Metabolism Is Essential For Adaptation To Oxygen Desupporting
confidence: 51%
See 1 more Smart Citation
“…Consistent with previous observations (30), the dosR mutant dramatically lost viability on induction of hypoxia. Complementation experiments have previously demonstrated that this phenotype is primarily, but not completely, due to loss of the ribosome-stabilizing factor RafH (32). Our experiments show that survival also depends on the combined activity of the three hydrogenases from M. smegmatis, all of which are up-regulated under oxygen limitation (14).…”
Section: Hydrogen Metabolism Is Essential For Adaptation To Oxygen Desupporting
confidence: 51%
“…Numerous components of the DosR regulon of M. smegmatis are also DosR dependent in pathogenic mycobacteria, including multiple universal stress proteins (30,31), a ribosome stabilizingfactor (32,33), and putative energy metabolism genes (e.g., diacylglycerol acyltransferases, nitroreductases) (34,35) (Tables S1 and S2). The DosR regulon of M. smegmatis also controls the expression of some genes that are not DosR dependent or are absent from the pathogen (Table S2), most notably 10 genes involved in hydrogen metabolism and 6 genes linked to sulfur metabolism ( Fig.…”
Section: Transcription Of Two [Nife]-hydrogenases Depends On Dosrmentioning
confidence: 99%
“…It is known that entry to the dormant state in Mtb, and other mycobacteria, is triggered by hypoxia and controlled by the DosR response regulator, which controls the expression of some 48 genes in Mtb (6,37). A study in Mycobacterium smegmatis has implicated two S30AE proteins from the dosR regulon as key mediators of ribosome stability during hypoxic stasis (38). Both have counterparts in Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that dosR regulon genes are up-regulated during dormancy and that they have important immunological roles [11,35] to play including their newly identified dormancy functions such as stabilization of ribosomes [19,36]. In order to find a new way to cure tuberculosis it is important to know the effect of virulence associated genes of the dosR regulon and their interaction with the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…DATIN is one of the strongly up-regulated genes in the dosR [8], the latter encompasses an essential set of genes needed for adaptation to stress conditions. While DATIN has a established role in translation control [19,36], its amino acid sequence presented with high antigenic index prompted us to look into its possible immunological/antigenic potential. Further, DATIN was earlier listed as a candidate to induce human T-cell responses [11].…”
Section: Discussionmentioning
confidence: 99%